Mengkonsumsi Makanan Halal Perspektif Al-Qur’an: Telaah Semantik-Historis QS Al-Baqarah ayat 168 - Afrizal El Adzim Syahputra; Nur Faizin; Abduloh Safik; Abul Ma'ali (AL QUDS : Jurnal Studi Alquran dan Hadis, 2023)
Consuming Halal Food from the Perspective of the Qur'an: A Semantic-Historical Study QS. Al-Baqarah verse 168This paper aims to analyze the meaning of halal in QS. Al-Baqarah (2) verse 168 with a semantic-historical approach. The enrichment of the concept of halal food in the Qur'an is important, especially for researchers in the field of Al-Qur'an and commentary. This research is a literature review with a semantic-historical analysis paradigm in QS Al-Baqarah (2): 168. This study found that based on a semantic approach, the word "halal" in this verse includes two words that are collocated (side by side) with the word "thayyib" . Halal consumption along with orders to stay away from satanic steps. This connotatively means that Allah SWT wants humans to be physically and spiritually healthy. Historically, this verse is related to the culture of Arab society which considers certain animals as sacred animals. They equate their position with the idols that are worshiped. This verse came down to rectify this wrong view